Distal‐type epitheloid sarcoma mimicking a wart in a child: A diagnosis not to be missed. Issue 1 (27th November 2020) - George, Kimberley; Morren, Marie‐Anne; Christen, Thierry; Letovanec, Igor; Christen‐Zaech, Stephanie
Abstract: Epithelioid sarcoma is a rare soft‐tissue tumor that occurs mainly in children and young adults. It typically presents as a subcutaneous or deep dermal mass in distal extremities. Due to its benign‐appearing clinical presentation, infrequent occurrence, and histologic similarities with other pathologies, the diagnosis of epithelioid sarcoma in its early stages can be extremely difficult and can be easily confused with benign lesions such as warts or foreign body granuloma. In this paper, we report the case of a 12‐year‐old boy with a distal‐type epithelioid sarcoma of the hand and wish to emphasize the difficulties of diagnosing this potentially lethal tumor both clinically and histologically.